PENERAPAN MODEL CTL BERBASIS KEJURUAN DENGAN MEDIA ENGINE COMPONENT UNTUK MENINGKATKAN KEMAMPUAN PENALARAN SISWA PADA MATERI LOGIKA MATEMATIKA DI KELAS X1 TEKNIK PENGELASAN SMK NEGERI 1 RAMBAH - Musnar Musnar (Indonesian Journal of Basic Education, 2019)
The background of the problem in this study is the students' reasoning ability in mathematics subjects in class X1 of Welding Engineering at SMK Negeri 1 Rambah which is still considered low. This is caused by several factors, including the learning model applied by the teacher is still conventional so students are less active in learning. In this study, the problem that was attempted to overcome was the students' reasoning abilities. Based on the theoretical study reviewed by researchers, students' reasoning abilities can be improved through vocational-based CTL models with media engine components. This study aims to improve students' reasoning abilities by applying the vocational-based CTL model with the engine component media on mathematical logic material in class X1 of Welding Engineering at SMK Negeri 1 Rambah in the academic year 2016/2017. The methodology of this research is Classroom Action Research (CAR) which consists of 2 cycles, with each cycle consisting of 2 meetings with an allocation of each 4x45 minute cycle. The results achieved in this study turned out to have increased from cycle 1 to cycle 2 with the average test scores of 75.16 to 83.23 and classical completeness 74% to 87%. Then from the results of observations of student activities, it was produced that there was an increase from cycle 1 to cycle 2 from the average value of activities of students 2.2 with a fairly good category being an average value of 3.1 with a good category. For this reason, the results of the study can be said to be successful because they have answered the performance indicators with a minimum of 70% completeness and minimal student activity categories.